A Novel Technique for Correcting a Flexible Internal Rotation Deformity Following Talectomy. Issue 2 (June 2015) - Joyner, LCDR Patrick W.; Vap, Alexander R.; Orr, Steven; Fitch, Robert D.
Abstract : Talectomy is a procedure that can be used to treat failed clubfoot corrective surgery. Talectomy helps to correct the equinovarus deformity by providing sufficient laxity to the foot. A complication of this procedure is the direct result of the increased laxity it is designed to increase. We report the surgical technique for correcting a rotational deformity of the ankle following talectomy. At one year follow-up, our technique provided a stable correction. Although this is a rare complication, this technique may be useful alone or in conjunction with other procedures for the foot and ankle.